Broken discrete and continuous symmetries in two dimensional spiral antiferromagnets - Mezio, Alejandro (2013)
We study the occurrence of symmetry breakings, at zero and finite temperatures, in the J1-J3 antiferromagnetic Heisenberg model on the square lattice using Schwinger boson mean field theory. For spin 1/2 the ground state breaks always the SU(2) symmetry with a continuous quasi-critical transition at J3/J1 ~ 0.38,from Neel to spiral long range order, although local spin fluctuations considerations suggest an intermediate disordered regime around 0.35 ~ J3/J1 ~ 0.5, in qualitative agreement with recent numerical results. At low temperatures we find a Z2 broken symmetry region with short range spiral order characterized by an Ising-like nematic order parameter that compares qualitatively well with classical Monte Carlo results. At intermediate temperatures the phase diagram shows regions with collinear short range orders: for J3/J1 < 1 Neel (pi,pi) correlations and for J3/J1 > 1 a novel phase consisting of four decoupled third neighbour sublattices with Neel (pi,pi)_4 correlations in each one. We conclude that the effect of quantum and thermal fluctuations is to favour collinear correlations even in the strongly frustrated regime.